2020
DOI: 10.1002/ls.1494
|View full text |Cite
|
Sign up to set email alerts
|

Tribochemical degradation of vacuum‐stable lubricants: A comparative study between multialkylated cyclopentane and perfluoropolyether in a vacuum ball‐on‐disc and full‐bearing tests

Abstract: In this study, the decomposition of a multialkylated cyclopentane (MAC) and a perfluoro-poly-ether (PFPE) lubricant was investigated in a ball-on-disc sliding test under vacuum and in a rolling contact fatigue (RCF) test on full bearings. In situ mass spectrometry was conducted to study the tribochemical formation of hydrogen in a steel-on-steel ball-on-disc sliding contact. Further investigations on lubricant degradation in rolling-sliding contact indicated fragmentation and oxidation reaction of the MAC oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In addition, this product group often exhibits high starting friction, which is problematic for the safe design of the drive technology [11]. There is also a risk that the MAC oils generate hydrogen through tribochemical reactions, which can lead to premature rolling bearing failures [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this product group often exhibits high starting friction, which is problematic for the safe design of the drive technology [11]. There is also a risk that the MAC oils generate hydrogen through tribochemical reactions, which can lead to premature rolling bearing failures [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…To minimize these costs, lubrication science has been focused on reducing friction, minimizing wear, evacuating heat, and removing contaminants. However, it is well known that lubricants can undergo thermal decomposition in response to the heat of friction or high operating temperatures, as well as tribochemical decomposition induced by the high activity of nascent steel surfaces [1][2][3][4][5]. It has been suggested that hydrogen generated by lubricant decomposition is also an important aspect of the hydrogen embrittlement of metal parts.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that an increase in the concentration of such additives improves the anti‐wear and anti‐seizure properties; however, at the same time, it causes a deterioration of resistance to fatigue wear. A comparison of the decomposition of multialkylated cyclopentane and perfluoro‐poly‐ether greases as a result of friction was presented by the authors of the publication 23 . The results of rolling contact fatigue studies showed that hydrogen assisted damage in multi‐alkylated cyclopentane‐lubricated bearings, and the perfluoro‐poly‐ether lubricated bearing did not show any damage despite the longer test duration.…”
Section: Introductionmentioning
confidence: 99%